Charisma™ virtual social training: A digital health platform and protocol - Johnson, Maria; Tate, Aaron M.; Tate, Kathleen; Laane, Sarah A.; Chang, Zhengsi; Chapman, Sandra Bond (Frontiers in Virtual Reality, 2022)
Low immersion virtual reality (LIVR) is a computer-generated, three-dimensional virtual environment that allows for authentic social interactions through a personal avatar, or digital representation of oneself. Lab-based delivery of LIVR social skills intervention has been shown to support social learning through controlled, targeted practice. Recent remote technological advancements allow LIVR-based social skills training to potentially overcome accessibility barriers by delivering to youth in their home. This study investigated the impact of 10-hours of Charisma™ Virtual Social Training (CHARISMA-VST), a LIVR-based intervention, on social skill changes in children and adolescents who struggle socially via either in-person or remote training protocols. Specifically, the aims examined both the impact of training location (in-person vs remote access) and diagnosis (parent report of autism spectrum disorder (ASD) diagnosis versus parent report of other non-ASD diagnosis) on objective measures of social skill change following CHARISMA-VST. Researchers delivered the CHARISMA-VST via Charisma 1.0, a customized virtual gaming environment. Sixty-seven participants (49 males, 18 females) between the ages of 9-17, with parent reported social challenges, completed 10, one-hour CHARISMA-VST sessions during which nine social cognitive strategies were taught and then practiced within a LIVR environment with interspersed social coaching. Four social cognitive domains were measured pre-post training: emotion recognition, social inferencing, social attribution, and social self-schemata. Results revealed improvements in emotion recognition, social inferencing, social attribution, and social self-schemata with medium to large effect sizes following the CHARISMA-VST. There was no moderating effect of training location on emotion recognition, social inferencing, and social self-schemata, suggesting comparable gains whether participants accessed the technology in their own homes or from a school or specialty center. There was no moderating effect of ASD versus non-ASD diagnosis on performance measures, suggesting CHARISMA-VST may be effective in improving social skills in individuals beyond its initially designed use focused on individuals with ASD. These encouraging findings from this pilot intervention study provide some of the first evidence of potential new virtual technology tools, as exemplified by CHARISMA-VST, to improve one of the most important aspects of human behavior – social skills and human connectedness in youth with a range of social competency challenges.